Consumption of Macronutrients, Body mass index, Smoking status with Physical Fitness at Palembang Police District - Podojoyo Podojoyo; Tria Erma Juliana; Susyani Susyani; Yuli Hartati; Muhamad Taswin; Zainal Abidin (Poltekkes Kemenkes Yogyakarta, 2022)
Physical fitness is the ability of the body to make adjustments to the physical burden given to members of the police in carrying out daily work without causing excessive fatigue and still be able to enjoy their free time. Components of physical fitness related to health and skills are cardiorespiratory, muscle endurance, muscle strength and body composition. The purpose of this study was to determine the relationship between macronutrient consumption, body mass index status, and smoking status with physical fitness at Palembang police district officers. Data of macro nutrients intake were collected using 24-hours recall. Physical fitness levels are measured using Cooper's way. The design of this study was Cross-sectional by taking a random sample of 56 male police officers. The analysis results using chi-square concluded that there is a relationship between energy intake, carbohydrate intake, with fitness level (p≤0.05). There is a relationship between body mass index and smoking status, and physical fitness (p≤0.05). There is no relationship between protein and fat intake with physical fitness status (p>0.05). The results of the multivariate analysis obtained the most dominant relationship with physical fitness levels is BMI status and smoking status. It is recommended that police members improve physical fitness status to take some exercises that are useful to enhance physical fitness levels, namely sit ups, push-ups, squat jumps to run or jogging regularly. Police officers control their ideal weight by eating a balanced diet and not smoking